Gender Role Portrayal in Television Advertisement: Evidence from Pakistan - Ali, Abid; ., Dileep Kumar; ., Muhammad Haroon Hafeez; ., Bushra Ghufran (Information Management and Business Review, 2012)
This study aims to observe the gender role portrayal in food and non-food television advertisement in Pakistan, in order to find out gender discrimination (if any) and association of gender with different content variables. Content analysis of selected TV commercials was used to fulfill the purpose of this study. Services of two independent coders (business graduates) were utilized to code content variables for a sample of 103 commercials (54 food and 49 non-food commercials). Based on the extant literature, seven content variables were selected for this study including: main product user, voiceover, primary character, end comment, soundtrack level, activity level and aggression level. The gender role portrayals in both food and non-food commercials have been compared and discussed. There exists gender discrimination in Pakistani television advertisement, where males dominate more. The reason behind this phenomenon is expected to lie in social and cultural values. This male dominance is higher in food advertisement as compared to non-food advertisement. Results also favor the association of male character with the relatively higher activity and aggression levels in television commercials. The findings of this study are supportive for key players in advertising industry like advertisers and advertising agencies, for self-regulation of their advertising campaigns with respect to gender role. However, more important implication for them is to know about the forces of traditional cultural values and preferences of target audience, for effective planning of the commercials and forecasting their impact. Such knowledge can provide them a better base to assess the need for self-regulation of their advertising campaigns, guiding them towards making more successful commercials. This study reflects the true picture of gender discrimination in Pakistani television advertisement. It has been concluded using a well defined methodology, provides original data for Pakistan and can be considered a good reference for further analysis.